Infertility and Intimacy in an Online Community - Billett, Paulina; Sawyer, Anne-Maree (Palgrave Macmillan Studies in Family and Intimate Life, 2019)
This book explores an online support group for women who are infertile. Offering a close-up view of the women's identities and emotions as they navigate the "roller-coaster" world of infertility, a range of questions are addressed: How do the women seek support? How do they offer support to one another? How are intimacies produced in the online space? Through narrative analysis of online journals and posts, the authors examine the impact of infertility on women's perceptions of their bodies, their struggles with medical professionals, on their relationships with family and friends, and the challenges that a diagnosis of infertility presents to couples. Infertility and Intimacy in an Online Community will appeal to social scientists, students from a range of health science disciplines, counsellors and health professionals, and women and men who are dealing with infertility. .